Reflective Teaching Practice: Insight(s) from Indonesia’s Pesantren - A'la, Bassam Abul; Sun, Xiaohui; Hilmy, Masdar; Suryani, Suryani (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Reflective teaching (RT) is a strategy used by teachers to improve their professionalism in the learning process. This indicator has long been debated and investigated in the field of education. However, few have examined the realm of Islamic education institutions, which have distinct qualities. As a result, the purpose of this study was conducted to investigate how teachers in Indonesian Islamic education institution implement RT. Quantitative questionnaires were administered via Google Forms, and semi-structured interviews were conducted via online focus group discussions (FGDs). This study included 19 pesantren teachers from Indonesia's Java, Sumatra, and Sulawesi Islands. The findings revealed that pesantren teachers used three types of reflection positively well. All the six RT indicators for teacher were proved to be significant. RT in Islamic education institution has been shown to apply Kyai's guidance as one of several techniques for improving teaching quality. However, the RT technique of writing a journal has not been generally adopted by teachers in pesantren.